PEMODELAN PEMILIHAN MODA TRANSPORTASI KERETA API KOMUTER EKSEKUTIF DAN KERETA API EKONOMI MALANG-SURABAYA - Dita Fitrianingsih; Dwi Ratnaningsih; Udi Subagyo (Prokons: Jurnal Teknik Sipil, 2022)
AbstractPT. KAI Daop 8 want to release the executive commuter train Malang-Surabaya and Surabaya-Malang to increase the passenger’s convenience and to suit the train’s passenger. The purpose of this journal is to know about the train’s mode choice between the Malang-Surabaya economy train and the Malang-Surabaya executive commuter train based on passenger interest.The required datas are the respondent’s questionnaires that were taken with Stated Preference technique and the total number of passengers of Malang-Surabaya and Surabaya-Malang economy train on 2016-2021. The analysis began by determining the minimum number of the respondent’s questionnaires, after that the questionnaires were shared, the questionnaires were processed with Microsoft Excel and the result was processed with SPSS 25.The results of the analysis show that the selected of the train’s mode choice based on passenger interest is (UKOM – ULOK) = -0,460 – 0,053X1 – 0,171X2, X1 is for the travel time difference of executive commuter train and existing train, X2 is for the cost difference of executive commuter train and existing train.Keywords: Commuter train, Stated Preference Method, Mode choice